2019
DOI: 10.1111/bjh.15887
|View full text |Cite
|
Sign up to set email alerts
|

The poor prognosis of low hypodiploidy in adults with B‐cell precursor acute lymphoblastic leukaemia is restricted to older adults and elderly patients

Abstract: Summary The prognostic significance of low‐hypodiploidy has not been extensively evaluated in minimal residual disease (MRD)‐oriented protocols for adult acute lymphoblastic leukaemia (ALL). We analysed the outcome of hypodiploid adult ALL patients treated within Programa Español de Tratamientos en Hematología (PETHEMA) protocols. The 5‐year cumulative incidence of relapse (CIR) of low‐hypodiploid B‐cell precursor (BCP)‐ALL was significantly higher than that of high‐hypodiploids (52% vs. 12%, P = 0.013). Low‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…It has been reported that pediatric patients with B-ALL with <36 chromosomes may show additional structural chromosome aberrations more frequently when compared with those with ≥36 [ 22 ]. It would be interesting to learn whether pediatric patients with additional structural alterations are also older than those without them, which would be consistent with different reports on adult B-ALL showing structural chromosome aberrations, especially unbalanced translocations and losses of chromosome arms, in 50% of low-hypodiploid cases [ 35 , 38 ].…”
Section: Cytogenetic Characterization Of B-all With Hypodiploidy <40 Chromosomessupporting
confidence: 75%
See 2 more Smart Citations
“…It has been reported that pediatric patients with B-ALL with <36 chromosomes may show additional structural chromosome aberrations more frequently when compared with those with ≥36 [ 22 ]. It would be interesting to learn whether pediatric patients with additional structural alterations are also older than those without them, which would be consistent with different reports on adult B-ALL showing structural chromosome aberrations, especially unbalanced translocations and losses of chromosome arms, in 50% of low-hypodiploid cases [ 35 , 38 ].…”
Section: Cytogenetic Characterization Of B-all With Hypodiploidy <40 Chromosomessupporting
confidence: 75%
“…Although traditionally defined as the loss of one or more chromosomes in a cell [ 34 ], hypodiploidy has been classified according to diverse criteria in different studies to define different hypodiploid B-ALL subtypes ( Table 3 ), and a clear distinction between those cases with <40 chromosomes and those with 40–45 chromosomes has become generally accepted based on the evident differences in treatment response [ 21 , 35 ]. Hypodiploid cases with <40 chromosomes can be further subdivided into two groups based on the bimodal distribution of chromosome numbers: (i) near-haploidy, with 24–29 chromosomes ( Figure 2 A), and (ii) low-hypodiploidy, with 30–39 chromosomes ( Figure 2 B,C) [ 27 ] ( Table 3 ).…”
Section: Cytogenetic Characterization Of B-all With Hypodiploidy <40 Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for patients who achieve MRD-negative status after induction, allogeneic transplantation has been shown to be not successful in improving overall survival [31,32]. Although MRD-oriented protocols, older adults and elderly patients with low hypodiploidy do fairly poor with higher five-year cumulative incidence of relapse compared to high hypodiploid cases [33], making them candidates for different treatment approaches (e.g., immunotherapy and targeted therapies). Among those, preclinical studies have shown that hypodiploid ALL cells are sensitive to Phosphoinositide 3-kinase (PI3K) and BCL2 Apoptosis Regulator (BCL2) inhibitors [27,34].…”
Section: Subtypes With Chromosomal Aneuploidymentioning
confidence: 99%
“…In this issue of the Journal, Ribera et al () present a retrospective study designed to determine the influence on prognosis of low‐hypodiploidy in 56 adults with Philadelphia chromosome (Ph)‐negative B‐cell precursor acute lymphoblastic leukaemia (ALL). The patients were treated on minimal residual disease (MRD)‐oriented Programa Español de Tratamientos en Hematología (PETHEMA) protocols between 1993 and 2017.…”
mentioning
confidence: 99%